Time continuum and true long-term ecology: from theory to practice - Rull, Valentí (Frontiers in Ecology and Evolution, 2014)
The need for long-term studies to understand ecological dynamics is widely recognised but has not been satisfactorily addressed to date. The development of “long-term” (LT) observatories has aimed to improve the situation, but the main handicaps are that we should wait for generations to yield reliable results and that a number of ecological processes occurring at time scales larger than centuries will not be fully resolved. Palaeoecology can provide the needed time scale for true long-term ecology, but it is limited by the ability to merge ecological and palaeoecological data into continuous time series. This paper suggests a practical way of attaining such goals based on the concept of time continuum. A short review is provided on the main handicaps for palaeoecological records to be incorporated into current ecological datasets and the recent improvements in the field. A global network of past-present-future ecological observatories (PPFEO) centered around lakes with annually-laminated sediments could act as a means of producing truly long-term and continuous ecological records by combining high-resolution palaeoecological techniques with ecological methods commonly used in LT observatories.